Multi-field modeling and simulation of fiber-reinforced polymers - Schulte, Jonathan (Schriftenreihe des Instituts für Mechanik, Karlsruher Institut für Technologie, 2023)
This work proposes a new numerical approach for analyzing the behavior of fiber-reinforced materials, which have gained popularity in various applications. The approach combines theories and methods to model the fracture behavior of the polymeric matrix and the embedded fibers separately, and includes a modified plasticity model that considers the temperature-dependent growth of voids. Tests are conducted to explore different types and sequences of failure in long fiber-reinforced polymers.